2018
DOI: 10.1007/s00417-017-3883-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the neuroinflammatory responses to selective retina therapy and continuous-wave laser photocoagulation in mouse eyes

Abstract: SRT resulted in selective RPE damage without collateral thermal injury to the neural retina, and apparently produced negligible glial activation. In addition, SRT showed a markedly less inflammatory response than cwPC, which may have important therapeutic implications for several macular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Four days after SRT, irregular shaped cells with conspicuous nuclei covered the laser-induced RPE wound (b). Some of these enlarged cells showed two nuclei (arrow), which suggest mitosis nificantly lower levels after SRT than in LPC [43]. It has also been shown that matrix metalloproteinases (MMPs), particularly the active form of MMP-2 is significantly upregulated [39,40,44] and also locally resolved as shown in Fig.…”
Section: Resultsmentioning
confidence: 85%
“…Four days after SRT, irregular shaped cells with conspicuous nuclei covered the laser-induced RPE wound (b). Some of these enlarged cells showed two nuclei (arrow), which suggest mitosis nificantly lower levels after SRT than in LPC [43]. It has also been shown that matrix metalloproteinases (MMPs), particularly the active form of MMP-2 is significantly upregulated [39,40,44] and also locally resolved as shown in Fig.…”
Section: Resultsmentioning
confidence: 85%
“…AMD treatment is diverse, involving neurotrophic factors, growth factors, cell viability factors, and also oxidative stress-preventing factors [ 2 , 29 , 30 , 31 ]. With the wet AMD, vascular endothelial growth factor (VEGF) inhibitors and the photodynamic therapy are mainly used [ 32 , 33 ]. Despite efforts aimed at developing adequate therapy, the challenges associated with the treatment of AMD to preserve vision are still substantial.…”
Section: Brief Characteristics Of the Major Degenerative Disorders Of...mentioning
confidence: 99%
“…On the other hand, the clinical efficacy of the neuroprotective strategies has not been firmly established. Furthermore, surgical interventions like laser therapies may not prevent the progression of the disease in patients with AMD or other RD and can cause inflammatory-related damages[ 37 - 39 ].…”
Section: Retinal Degenerations and Treatmentsmentioning
confidence: 99%